A comprehensive review on immunosuppressant agent: Tacrolimus - Pole, Sushama; Athawale, Rajani; Bhupathyraaj, Mullaicharam (Journal of Neonatal Surgery, 2025)
An immunosuppressive drug with great potency, tacrolimus (FK 506), has been shown to be effective in both in-vivo and in-vitro studies. As a calcineurin inhibitor, tacrolimus is also effective. The pharmacokinetics profile of tacrolimus is very variable across and within patients as a result of its low solubility. Numerous formulation strategies, including complexation with cyclodextrins, solid dispersions, oily solutions, liposomes, etc., have been researched to increase this agent's oral administration. Tacrolimus can be used to treat severe autoimmune disorders such atopic dermatitis and rheumatoid arthritis, and it has been given for patients who have undergone liver, intestine, lung, and heart transplants. Because it has a superior safety profile and a higher rate of long-term survival in patients than other immunosuppressants, tacrolimus is used the most commonly..